Peranan Career Anchor dalam Menciptakan Kepuasan Kerja Pegawai Dinas Perindustrian dan Perdagangan Kota Lubuklinggau - Irma Idayati; Hardi Mulyono; Yonathan Panji Kristian (IPM2KPE, 2023)
This study aims to determine the role of Career Anchor on Job Satisfaction. This study uses a quantitative approach. The method of determining the location in this study deliberately has a high popularity. Sampling used a survey method where a population of 50 employees was used as a sample. Data collection tool using a questionnaire. Testing data analysis using the help of the SPSS version 23 application in 2020. The results of this study show that the Career Anchor variable (X) on performance shows a tcount = 6.205 greater than the ttable = 2.010 with a significant level = 0.000 <0.05. In conclusion, Career Anchor influences and plays a role in job satisfaction at the Office of Industry and Trade of Lubuklinggau City. Keywords: Career Anchor, Job Satisfaction